Impact of prediabetes and duration of diabetes on radial artery atherosclerosis in acute coronary syndrome patients: An optical coherence tomography study. (9th February 2022) - Li, Zixuan; Tang, Zhe; Wang, Yujie; Liu, Zijing; Wang, Senhu; Wang, Yuntao; Wang, Guozhong; Wang, Yuping; Guo, Jincheng
Background: Prediabetes (PDM) and diabetes mellitus (DM) are common among acute coronary syndrome (ACS) patients. The present study evaluated the association between diabetes status and radial artery (RA) atherosclerosis using optical coherence tomography (OCT) in ACS patients. Methods: A total of 335 ACS patients who underwent RA OCT were categorized into the DM group, the PDM group, and the normal glucose metabolism (NGM) group. OCT characteristics and clinical variables were compared. Results: RA atherosclerotic plaques were more frequent in the PDM and DM groups than in the NGM group (38.7% vs. 33.3% vs. 16.1%, p = 0.001). Lipid and calcified plaque occurrence were significantly more common in the DM group, followed by the PDM and NGM groups (19.3% vs. 14.6% vs. 6.5%, p = 0.027; 11.8% vs. 6.5% vs. 1.1%, p = 0.009). The prevalence of microvessels in the PDM group was significantly higher (42.7% vs 23.7%, p = 0.017) than in the NGM group but was comparable to the DM group. Multivariate analysis revealed that HbA1c level and age were independent predictors of RA plaque formation and eccentric intimal hyperplasia (all p <0.05). Conclusions: RA atherosclerosis characteristics differ according to diabetes status. HbA1c level could be a useful marker for RA atherosclerosis progression in ACS patients.